A New Look at the Structure of Genitive and Attributive Similes with a Special Emphasis on Hafez’s Poems - Meysam Hajipour; Enayatollah Mahmoodi (مطالعات زبانی و بلاغی)
Simile is one of the most important and useable fictional elements in prose and poem. This fictional element has been the poets’ and educators’ means to show their artistic skills in various ways. One of the ways of using similes is to include the simile elements in the structure of a noun category. Noun categories are the grammatical units, the core of which is a noun; and they are usually modified by a number of preceding or following modifiers. Noun categories, which comprise two different structures of genitive compounds (noun-noun) and attributive compounds (adjective-noun), can include the elements of simile. So far, the genitive similes with the structure of the genitive compound have been paid attention to. They have been made equivalents to the genitive eloquent simile in all of the recent rhetoric and eloquent works. However, this article puts forth reasons to show that it is not acceptable. Moreover, no word has been made in the early and recent books of eloquence about the similes with the attributive compounds. This study tries to investigate both noun categories of simile (compounds of genitive and attributive similes) with the help of new grammars and based on linguistics with a special emphasis on Hafez’s poems.